Assisted reproductive technology in Australia and New Zealand: cumulative live birth rates as measures of success. Issue 3 (24th July 2017) - Chambers, Georgina M; Paul, Repon C; Harris, Katie; Fitzgerald, Oisin; Boothroyd, Clare V; Rombauts, Luk; Chapman, Michael G; Jorm, Louisa
Abstract: Objectives: To estimate cumulative live birth rates (CLBRs) following repeated assisted reproductive technology (ART) ovarian stimulation cycles, including all fresh and frozen/thaw embryo transfers (complete cycles). Design, setting and participants: Prospective follow‐up of 56 652 women commencing ART in Australian and New Zealand during 2009–2012, and followed until 2014 or the first treatment‐dependent live birth. Main outcome measures: CLBRs and cycle‐specific live birth rates were calculated for up to eight cycles, stratified by the age of the women (< 30, 30–34, 35–39, 40–44, > 44 years). Conservative CLBRs assumed that women discontinuing treatment had no chance of achieving a live birth if had they continued treatment; optimal CLBRs assumed that they would have had the same chance as women who continued treatment. Results: The overall CLBR was 32.7% (95% CI, 32.2–33.1%) in the first cycle, rising by the eighth cycle to 54.3% (95% CI, 53.9–54.7%) (conservative) and 77.2% (95% CI, 76.5–77.9%) (optimal). The CLBR decreased with age and number of complete cycles. For women who commenced ART treatment before 30 years of age, the CLBR for the first complete cycle was 43.7% (95% CI, 42.6–44.7%), rising to 69.2% (95% CI, 68.2–70.1%) (conservative) and 92.8% (95% CI, 91.6–94.0) (optimal) for the seventh cycle. For women aged 40–44 years, the CLBR was 10.7% (95% CI, 10.1–11.3%) for the first complete cycle, rising to 21.0% (95% CI, 20.2–21.8%) (conservative) and 37.9% (95% CI, 35.9–39.9%) (optimal) for the eighth cycle. Conclusion: CLBRs based on complete cycles are meaningful estimates of ART success, reflecting contemporary clinical practice and encouraging safe practice. These estimates can be used when counselling patients and to inform public policy on ART treatment.